Fenomena Jasa Titip dan Perubahan Pola Belanja Konsumtif di Media Sosial Tiktok oleh Generasi Muda di Perkotaan : (Studi pada Mahasiswa di Jakarta Selatan) - Vinta Sevilla; Zayyin Abdul Quddus; Gustiana Sabarina; I Nyoman Aji Suadhana Rai (FISIP UPNVJ, 2026)
The development of digital media and platforms is driving changes in the shopping habits of the younger generation, particularly in the practice of shopping through personal shopping services (jastip) on TikTok. This research is motivated by the increasing tendency of the younger generation to utilize digital media as a primary reference for fulfilling shopping needs. This study aims to explore the phenomenon of the habit of using personal shopping services (jastip) on TikTok by the younger generation, and changes in the pattern of impulsive shopping habits of the younger generation through TikTok. The research location was chosen in South Jakarta because this area has a high level of internet usage, the characteristics of the younger generation who are adaptive to trends, and the intensity of social media use for shopping. This study used a descriptive qualitative method with data collection techniques through in-depth interviews with young users of personal shopping services. The results of this study indicate that the use of personal shopping services is based on limited access and time, urgency of needs, economic efficiency, media promotional stimuli, and trust in personal shopping providers. Personal shopping services (jastip) are used as a solution to obtain exclusive products, both domestic and international, at various prices. Exposure to personal shopping content on TikTok also encourages a shift in shopping behavior towards a more impulsive direction, which does not only look at rational needs, but also emotional drives and trends. The conclusion of this study shows that the phenomenon of jastip on TikTok involves rational considerations and the influence of social media in shaping the shopping behavior of the younger generation and it is hoped that the younger generation can improve digital literacy by having awareness of good and appropriate shopping consumption.